Boosting the local anodic oxidation of silicon through carbon nanofiber atomic force microscopy probes - Rius, Gemma; Lorenzoni, Matteo; Matsui, Soichiro; Tanemura, Masaki; Perez-Murano, Francesc (Beilstein Journal of Nanotechnology, 2015)
Many nanofabrication methods based on scanning probe microscopy have been developed during the last decades. Local anodic oxidation (LAO) is one of such methods: Upon application of an electric field between tip and surface under ambient conditions, oxide patterning with nanometer-scale resolution can be performed with good control of dimensions and placement. LAO through the non-contact mode of atomic force microscopy (AFM) has proven to yield a better resolution and tip preservation than the contact mode and it can be effectively performed in the dynamic mode of AFM. The tip plays a crucial role for the LAO-AFM, because it regulates the minimum feature size and the electric field. For instance, the feasibility of carbon nanotube (CNT)-functionalized tips showed great promise for LAO-AFM, yet, the fabrication of CNT tips presents difficulties. Here, we explore the use of a carbon nanofiber (CNF) as the tip apex of AFM probes for the application of LAO on silicon substrates in the AFM amplitude modulation dynamic mode of operation. We show the good performance of CNF-AFM probes in terms of resolution and reproducibility, as well as demonstration that the CNF apex provides enhanced conditions in terms of field-induced, chemical process efficiency.
Keywords: carbon nanofiber; dynamic mode; local anodic oxidation; nanopatterning